Ochrona tymczasowa parku, ogrodu lub innej formy zaprojektowanej zieleni zabytkowej objętej postępowaniem o wpis do rejestru zabytków w świetle aktualnej wykładni przepisów - Pyrzyk, Aleksander (Studia Prawa Publicznego, 2025)
The temporary protection of parks, gardens, or other forms of designed historic green spaces that are subject to proceedings for registration in the heritage register is currently regulated by Article 10a of the Act on the Protection of Monuments and the Care of Monuments. This provision, introduced by the 2017 amendment, has been the subject of numerous discussions, doctrinal disputes, and statements by the Commissioner for Human Rights. Over the years, the jurisprudence has developed a number of analyses of the interpretation of this provision, which has not been amended to this day. This article focuses on parks, gardens, and other forms of historic greenery that have been included in the proceedings for registration in the heritage register. Starting from a narrow issue allows for a better understanding of the importance of the problem being dealt with, drawing attention to a more universal issue – relating to the proceedings for the registration of other properties listed in Article 6(1)(1) of the Act of 23 July 2003 on the Protection of Monuments and the Care of Monuments. The analysis of the application of Article 10a of the Act on the Protection of Monuments and the Care of Monuments is preceded by an explanation of the rationale for introducing the regulation. Then, the discussion turns to the practical functioning of this provision. The practice of applying temporary protection, along with numerous rulings by administrative courts, highlights both the strengths and weaknesses of the provision. Over the years, solutions have been found to the doctrinal disputes discussed in this article. Moreover, certain interpretative doubts or the lack of regulation on all issues crucial for the protection and preservation of heritage are also addressed, along with proposals for legislative changes in the future.